Synthesis of enones, pyrazolines and pyrrolines with gem-difluoroalkyl side chains - El Dine, Assaad Nasr; Khalaf, Ali; Grée, Danielle; Tasseau, Olivier; Fares, Fares; Jaber, Nada; Lesot, Philippe; Hachem, Ali; Grée, René (Beilstein Journal of Organic Chemistry, 2013)
Starting from easily accessible gem-difluoropropargylic derivatives, a DBU-mediated isomerisation affords enones in fair yields with a gem-difluoroalkyl chain. These derivatives were used to prepare pyrazolines and pyrrolines with the desired gem-difluoroalkyl side chain by cyclocondensations in good yields and with excellent stereoselectivity. A one-pot process was also successfully developed for these sequential reactions. By carrying out various types of Pd-catalyzed coupling reactions for compounds with a p-bromophenyl substituent a route to focused chemical libraries was demonstrated.
Keywords: 19F/1H HOESY; gem-difluoroalkyl derivatives; organo-fluorine compounds; palladium catalysis; pyrazolines; pyrrolines